Fecal Ciliate Composition of Domestic Horses (Equus caballus Linnaeus, 1758) Living in Kyrgyzstan - Gürelli̇ Gözde; Canbulat, Savaş; Aldayarov, Nurbek (Zootaxa, 2015)
Species composition and distribution of intestinal ciliates were investigated in the feces from 15 domestic horses living in Bishkek, Kyrgyzstan. Twenty-three species belonging to 14 genera were identified. This is the first study on intestinal ciliates in domestic horses living in Kyrgyzstan. The mean number of ciliates was 14.1 ± 6.8 x104 cells ml-1 of feces and the mean number of ciliate species per host was 6.0 ± 3.2. No endemic or new species were detected. Blepharocorys was the major genus as these ciliates were detected in high proportions. In contrast Holophryoides, Allantosoma were only observed at low frequencies. Recorded ciliate species in this investigation had almost the same characteristics as those described in previous studies. There was no important geographic variation in the intestinal ciliate fauna of equids.